As estratégias de criação e convencimento da realidade: um estudo de caso do documentário Super Size Me - Roncador, Natália Lázaro (2019)
The expectation of the public to find different sources of information, reliable and independent of economic and political influences has the consequence of increasing production and search for documentary narratives. In order to renew its sources of reference and reading of the world, the public begins to consume in the demand to acquire a real picture of reality. However, the documentarist, in the position of filmmaker, although he has attention with the facts, the freedom to choose a point of view allows him a look at the truth reported. It is the construction of narrated reality, of an ideological perception of the director figured in a cinematographic production. Thus, it is relevant to know what are the strategies predominant to the non-fiction film capable of convincing the public about the veracity of a reality cut. In this attempt, we chose to study a film of great repercussion by the specialized, the documentary Super Size me (Morgan Spurlock, USA, 2004).